UMA ESCOLA PELO AVESSO: EXPERIMENTAÇÕES EM UM GLOSSÁRIO DIFRATIVO - Lucas Ferreira Gomes (2025)
This thesis entangles agencies that constitute a school in the final years of Elementary Education and in High School, through a post-qualitative research approach. The aim is to produce diffractive readings of a school as a space–time–matter phenomenon in emergence. Diffractive readings with/about/from/of (always) a school. In parallel (diagonally, transversally)—and not hierarchically—dialogues and conversations are carried out with Agential Realism, in unfoldings with productions of the so-called New Materialism. The investigation takes place at Colégio Estadual Santa Maria Goretti, in Maringá (PR), and unfolds as a diffractive glossary, in which each entry functions as an agential cut that composes and displaces the potentials of what a school can be. Entangled with Karen Barad’s Agential Realism and propositions of New Materialism, the research takes diffractive reading as method, ethics, and politics of knowledge production. Diffraction invites inhabiting patterns of interference and resonance, destabilizing dualisms between subject and object, theory and practice, researcher and field, theory and analysis, introduction and final considerations. The writing risks being with the school, allowing itself to be affected, as well as affecting, by the materialities, bodies, silences, affects, and contradictions of everyday life. The glossary does not organize concepts but sustains events. The readings do not produce results, but compositions that emerge in the folds of movement. Some words were savored (ingested, traversed, sparked) as gestures that sustain reverberations—mourning, precarity, exteriority–inside, multispecies kin, anguish—without fixing meanings. Others remain unnamed, vibrating in the hallways, in the lines, in the lessons that fail and remake themselves, in the disappearances and insistences that traverse the school. What emerges is not a single school, but multiple ones—made of accumulations and losses, normativities and ruptures, presences that do not fit into protocols. Goretti presents itself as insistence: a school that intra-acts with crisis and, still, continues to make itself space-lives. It is a school in invention, where learning and unlearning happen together, where the researcher is also data (implicated, affected, transformed). Cuts are invented (human and non-human) that open questions. This thesis does not conclude: it reverberates, remains in suspension, vibrates and escapes, continuing as a means of conversation and an opening to what may still emerge from a school inside out.